The Temperature-analysis Influence on Fatigue Crack Growth Behaviour of Magnesium Alloy - A. Fauthan, M.; Abdullah, S.; F. Abdullah, M. (International Journal of Engineering and Technology, 2018)
In this study, the temperature-based mechanical fatigue crack growth of a magnesium alloy was investigated. Since fatigue is an irreversible process and experience temperature change, the fatigue crack growth behaviour of AZ31B was investigated based on the temperature trend. For this objective, compact tension tests were carried out by applying different stress levels to the specimen. The temperature trend was monitored via an infrared sensor. During the cyclic load applied to metallic materials, mechanical energy is expended to bring about plastic deformations at a macroscopic level. At the point of fracture, there was a temperature increase of 2.2ËšC when 5.12MPa stress level is applied. This temperature increase was due to the generation of thermal energy from the dislocation motion and grain friction on the material under cyclic loading which has caused an increase in the internal molecular average energy of the material. Thus, the temperature trend could be a new indication of fatigue crack growth behaviour.Â Â